An architectural monograph : wooden architecture in the Berkshires / by Roger Wearne Ramsdell ; prepared for publication by Russell F. Whitehead. - Ramsdell, Roger Wearne. (Tufts University. Tisch Library., 2020)
1 online resource (16 pages) : illustrations.; Tisch In-House Digitization 2019-12-29